ZVUKOVI ŠUTNJE U DOKTORU ŽIVAGU BORISA PASTERNAKA (Philological Studies, 2019)
Influence of classical music, and composers like Scriabin and Wagner, is clearly visible in the syntax and phonology of Pasternak’s poetical language. The relationship between musicality – rhythm, melody, sound, but also silence – is one of the focal points of literary language in his famous novel Doctor Zhivago, one of the greatest novels about the fall of Imperial Russia, and the end of the monarchy in bloody war and revolution ever written. This presentation aims to investigate some aspects of the relationship between art, violence, and revolution, i.e. between imaginary world of revolutionary (Soviet) Russia in Doctor Zhivago and the ways in which the novel represents these events through sounds of a crowd and city in turmoil, but even more importantly – through intense moments of silence. While the representation of Russian revolution as an event of intense sounds, even noisiness (as A. Blok writes in his essay Intelligentsia and Revolution, artist's duty was to create new literary forms and new language by grasping an extraordinary music of the Revolution), and therefore through audible and visual images of dramaturgy of sounds and cacophony, Pasternak's revolution in Doctor Zhivago is often portrayed through moments of silence, or protagonists' whisperings among themselves. Departing from the thesis that sounds and silence are physical states, but also an aesthetic and cultural devices, the aim of this paper is to answer the following questions. What are the meanings of sounds, silence, and whispering as metaphors of violence, war, and revolution in Pasternak's Doctor Zhivago? Especially in relation to “paradoxical materiality” (Ch. Miller) of silence, where this state of complete muteness and stillness represents at the same time emptiness – but also plentitude, weightlessness – but also heaviness, and therefore, as Miller further elaborates, “can (...) be seen as a simultaneous weightlessness (a dissolution of corporeal limits) and kinetic plenitude,” the paper analyzes the symbolism of moments of silence in Pasternak’s novel. Is Pasternak’s profound “rhetoric of silence” (C. Glenn) signifier of an amputation of Doctor Zhivago’s protagonists from the world of violent revolutionary Russia into their own, private, intimate worlds of introspection, or it is rather a signifier of their powerful resistance against general misrepresentation of revolution as universal political and cultural project of emancipation and freedom? In other words, can Pasternak’s “rhetoric of silence” in Doctor Zhivago be understood as a state of plentitude and knowing (S. Sontag), i.e. as a method of radical speech of silenced and whispering protagonists rather than of their muteness as a consequence of their (bourgeois) laid-backness and passivity?
Keywords: Boris Pasternak, Doctor Zhivago, silence, revolution, war, violence, literary device.